Multimedia in the wild: Testing the validity of multimedia learning principles in an art exhibition. (June 2018) - Schwan, Stephan; Dutz, Silke; Dreger, Felix
Highlights: Principles of multimedia learning are validated under conditions of informal learning settings. Participants visited a laboratory art exhibition with short labels, interpretive labels, a mobile guide, or an audio guide. Retention for pictorial details and text information was better for spoken than for written text. Extended text information increased memory for pictorial details.